The effect of product quality, price and product availability upon the purchasing decision to buy electricity cable of kabel metal brand in the area of DKI Jakarta (Case Study at PT. KMI Wire and Cable Tbk.) - Supriyatno .; S. Hartoyo (STIE Binaniaga, 2020)
This research aims to figure out the effect of Product Quality, Price and Stock Availability upon the Decision to Purchase Cable of Kabelmetal brand in DKI Jakarta. (Case Study at PT KMI Wire and Cable Tbk). Sampling technique of this research is sampling probability using Simple Random Sampling. This research has applied 100 respondents using quantitative descriptive approach and is located in DKI Jakarta. Therefore, data analysis has applied statistical analysis of multiple linear regression test. Data is processed by using SPSS Version 21. Result of analysis using SPSS version 21 indicates that only two of the three hypotheses have affected significantly. Result of the research has identified that Product Quality has affected significantly the Purchasing Decision which is 0.005 < 0.05 and Price has affected the Purchasing Decision which is 0.000 < 0.05. However, the hypothesis that has not affected the Purchasing decision is Product availability which value is 0.529 > 0.05. Keywords: Product Quality, Price, Product Availability, Purchasing Decision.